Quality of Life of Women with Polycystic Ovary Syndrome - Natalia Ligocka; Karolina Chmaj-Wierzchowska; Katarzyna Wszołek; Maciej Wilczak; Katarzyna Tomczyk (Medicina, 2024)
Background and Objectives: Polycystic ovary syndrome (PCOS) is an endocrine disorder characterized by multiple hormonal and metabolic abnormalities, including insulin resistance, hyperandrogenism, and disturbances in lipid and carbohydrate metabolism. The objective of this study is to assess the quality of life of women diagnosed with polycystic ovary syndrome (PCOS) and to identify any factors within the study group that may impact the scores related to quality of life. Materials and Methods: This research was carried out among women diagnosed with PCOS. An original questionnaire, developed through an online Google Forms survey, was utilized as the research instrument and distributed through social networks and support groups to women facing PCOS. This study encompassed a participant pool of 200 women with PCOS, aged 24 years or older. For the analytical component, Pearson’s χ2 test was employed—a nonparametric test designed to assess the relationship between two variables measured on a qualitative scale. The chosen level of statistical significance was set at p < 0.05. Results: The analysis revealed that the quality of life of the women under study was not linked to the duration of the disease or comorbidities. However, a significant association was observed with the inconvenience caused by PCOS symptoms. Women experiencing very bothersome symptoms of PCOS reported a lower quality of life compared to those with symptoms rated as not very bothersome. Despite the majority of women with PCOS rating their quality of life as good or very good, they often find the associated symptoms of PCOS bothersome. Women reporting lower quality of life tend to acknowledge the impact of PCOS on their lives, experience a sense of lack of control over the disease, struggle with depression, and do not accept their physical appearance. Conclusions: Hence, the support from specialists like endocrinologists, gynecologists, and nutritionists becomes crucial for many women dealing with PCOS. Adopting a healthy lifestyle, incorporating a balanced diet, and engaging in regular physical activity can assist in managing the troublesome symptoms of PCOS, thereby enhancing overall quality of life. In instances of emotional difficulties, seeking psychological support is equally important, and the significance of support and acceptance from loved ones should not be overlooked.